Factors Influencing Suicidal Ideation According to the Deprivation Indices of Different Regions in Korea - Yun-Young Kim; Hyung-Joo Park (Korean Society for Preventive Medicine, 2023)
Objectives This study examined how deprivation differed by region and the effect those differences had on suicidal ideation among the local population. Methods Data collected over 10 years (2012-2021) in the Korea Welfare Panel Study were organized into 3 categories: metropolitan, city, and rural. A panel analysis was conducted on the impact of deprivation indices, socio-demographic characteristics, and life satisfaction on suicidal ideation in each category. Results Income, divorce status, family relationship satisfaction, and medical deprivation had a significant impact on suicidal ideation in metropolitan areas, whereas these variables did not have significant effects in rural areas. In other words, income, family, and medical support were more impactful in city areas. Conclusions Although the deprivation index was higher in rural areas than in city areas due to an aging population and reduced income levels, the mental health of rural residents was found to be generally better than that of city residents. The possibility that this is related to the strength of relationships within the respective communities should be considered in light of recent discussions on relational welfare.